Inhibitory Effects of Pretreatment with Radon on Acute Alcohol-Induced Hepatopathy in Mice - Teruaki Toyota; Takahiro Kataoka; Yuichi Nishiyama; Takehito Taguchi; Kiyonori Yamaoka (Hindawi Limited, 2012)
We previously reported that radon inhalation activates antioxidative functions in the liver and inhibits carbon tetrachloride-induced hepatopathy in mice. In addition, it has been reported that reactive oxygen species contribute to alcohol-induced hepatopathy. In this study, we examined the inhibitory effects of radon inhalation on acute alcohol-induced hepatopathy in mice. C57BL/6J mice were subjected to intraperitoneal injection of 50% alcohol (5 g/kg bodyweight) after inhaling approximately 4000 Bq/m3 radon for 24 h. Alcohol administration significantly increased the activities of glutamic oxaloacetic transaminase (GOT), glutamic pyruvic transaminase (GPT) in serum, and the levels of triglyceride and lipid peroxide in the liver, suggesting acute alcohol-induced hepatopathy. Radon inhalation activated antioxidative functions in the liver. Furthermore, pretreatment with radon inhibited the depression of hepatic functions and antioxidative functions. These findings suggested that radon inhalation activated antioxidative functions in the liver and inhibited acute alcohol-induced hepatopathy in mice.